2016
DOI: 10.1016/j.proche.2016.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Activated Carbon Produced from Kenaf Core Fiber Using H3PO4 Activation

Abstract: Kenaf core fiber (KF) which is an agricultural biomass was used to produce low-cost activated carbon using acidic chemical activating agent. The aim of this study is to find out the changes occuring in kenaf core fiber during activation with phosphoric acid (H3PO4). The surface area of the formed phosphoric acid treated kenaf core fiber activated carbon (KFAC) was determined by physical adsorption of N2 gas. Brunauer, Emmett and Teller (BET) surface area, and micropore volume values were 299.02 m 2 /g and 0.12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
93
0
14

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 236 publications
(121 citation statements)
references
References 32 publications
14
93
0
14
Order By: Relevance
“…The weak absorptions between 1500 and 1260 cm -1 in ribbon fibres (Figure 4) arose from the aromatic ring vibrations with C-O stretching in lignin. The findings of this study were in agreement with the reported data on FTIR spectra of raw kenaf fibre (KF) by Shamsuddin et al (2016) Mechanical characterization of retted Kenaf fibres: stream retted Kenaf fibres had the highest tensile strength followed by tank retted fibres while ribbon fibres recorded the least.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The weak absorptions between 1500 and 1260 cm -1 in ribbon fibres (Figure 4) arose from the aromatic ring vibrations with C-O stretching in lignin. The findings of this study were in agreement with the reported data on FTIR spectra of raw kenaf fibre (KF) by Shamsuddin et al (2016) Mechanical characterization of retted Kenaf fibres: stream retted Kenaf fibres had the highest tensile strength followed by tank retted fibres while ribbon fibres recorded the least.…”
supporting
confidence: 92%
“…Kenaf possess two kinds of fibres and each of these fibres has different potentials to be explored. For instance, Shamsuddin et al (2016) highlighted that kenaf core fibre was used to produce activated carbons (AC). The long fibre contains approximately thirty percent (30%) of the total volume of kenaf plant whereas the short fibre represents the remaining of seventy percent (70% (Kuroda et al 2005)).…”
Section: Introductionmentioning
confidence: 99%
“…A high band at 1566.99 cm −1 could be allocated to CCC stretching vibration of the aromatic ring, which shifted to 1570.45 cm −1 after Pb(II) biosorption. An additional band at 1448.86 was observed after Pb(II) biosorption, which was also assigned to aromatic compound (CC) stretching in the aromatic ring . The peak at 1398.56 cm −1 is attributed to NO stretching vibration.…”
Section: Resultsmentioning
confidence: 95%
“…It was observed from the spectra (Fig. (a)) that the CH vibrations at 2919.69 and 2851.25 cm −1 (before Pb(II) adsorption) disappeared after Pb(II) adsorption, which showed the possibility of the aliphatic group associated with biosorption process . The peaks indicated at 2324.08 and 1844.02 were viably assigned to NH vibrations .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation